DECOMPOSITION RATE OF Sonneratia alba MANGROVE LEAF LITTERS IN THE COASTAL AREA, KARIMUN REGENCY KEPULAUAN RIAU PROVINCE - Rizki, Sofia Wanda; Tanjung, Afrizal; Nurrachmi, Irvina (Asian Journal of Aquatic Sciences, 2022)
Mangroves are plants that have an important role in providing very complex and potential food components for the life of various things at there and terrestrial biota. Mangrove's high productivity is obtained from litter. This study aims to determine the rate of litter decomposition and the percentage of the leaf decomposition of Sonneratia alba mangroves in the Coastal area. This research was conducted from August to September 2021. The method used in this study was an experimental method, where mangrove leaf fall was taken and observed the decomposition rate of S.alba mangrove leaf litter in the field for 28 days, and then dried the mangrove leaf. S.alba at the Marine Chemistry Laboratory, Faculty of Fisheries and Marine, Universitas Riau. Based on observations, it can be seen that the average temperature value ranges from 29.7 to 30.7˚C. The temperature at station I is relatively low compared to the other two stations. The measurement of the degree of acidity (pH) obtained the same results at each station, namely 7. For the measurement of salinity, the average obtained ranged from 34.3-35 ppt. The highest salinity known to be at station III is 35 ppt. In the measurement of Dissolved Oxygen (DO) the average value was obtained, which ranged from 4.60-5.89 mg/l. The decomposition process of S.alba leaf dregs which was carried out for 28 days showed that of rate of decomposition of S.alba mangrove leaf litter between stations, the highest rate of decomposition, is at station II an average of 3.92 g/day with a percentage of decomposition. 81.9% while at station III the average decomposition rate obtained was 3.35 g/day with a decomposition percentage of 75.8% and at station I is the station with the lowest rate of decomposition, which has an average of 3.25 g/day with a decomposition percentage of 67.0%.